Numerical Investigation of Relationship between Bursting Proneness and Mechanical Parameters of Coal - Hongwei Wang; Jiaqi Song; Zeliang Wang; Yue Zhang; Shaozhen Zhang; Yaodong Jiang (Shock and Vibration)
As one of the most catastrophic dynamic hazards in underground coal mines, coal bursts have been a major safety concern around the world for many years. Although the coal bursts can occur in all cases of hard to soft coal if the right stress environment is created, the occurrence of coal bursts is closely related to the intrinsic mechanical properties of coal, such as the bursting proneness. In this study, a total of 27 coal specimens are selected in the open literature studies to obtain a group of fundament data, such as the mechanical parameters, four bursting proneness indices, stress-strain curves, and their geological conditions where the specimens were taken. The relationship between bursting proneness indices and the cohesion of the coal specimens is established by numerically fitting the stress-strain curves and theoretically deduction. By taking into account the coal heterogeneity, eight probability distribution functions are employed to assignment nonuniform cohesion to the numerical model and to study the influence of heterogeneity on bursting proneness. The results reveal that the coal cohesion, which combines the common advantages of the four proneness indices, can be used as bursting proneness index. In the research of heterogeneity, the coal bursting proneness will decrease with the increasing of cohesion scatter degree. The larger the cohesion scatter degree increase is, the lower the bursting proneness will be. The failure of coal specimen is more and more severe with the decrease of cohesion scatter degree. In addition, this paper provides two methods for assigning heterogeneous parameters to the numerical model. The contours of shear strain rate and plastic state between homogeneous and heterogeneous coal specimens are compared to study the failure types of coal specimens and to reveal the mechanism of violent failure in coal bursts.